IMPLEMENTASI PENDIDIKAN AGAMA ISLAM SEBAGAI PILAR PENTING DALAM PEMBANGUNAN KARAKTER - Abdul Rozak (Universitas Islam Depok, 2024)
The implementation of Islamic Religious Education (PAI) as an important pillar in building student character in elementary schools is the main focus of this research. Using qualitative methods and case study approaches, this study aims to explore how PAI is implemented and its impact on student character building. Through data collection from observations, interviews, and documentation, comprehensive analysis can be performed to deeply understand the process and effects of PAI implementation. In this study, the implementation of PAI was seen through various programs and activities at PKPPS Minhajurrosyidin East Jakarta Class VI Ula. In addition to classroom learning, PAI is also integrated in extracurricular coaching and daily habituation. This shows that religious education does not only occur in the classroom, but also through student interaction in the school environment. Therefore PAI became more than just a subject. The results of the study confirmed that PAI has an important role in building student character. Through religious learning, students are taught religious values that become the moral foundation in their lives. In addition, aspects of honesty, responsibility, and discipline are also emphasized in PAI learning.